ANALISIS PENGARUH WAKTU TAHAN (HOLDING TIME) TERHADAP KEKERASAN BAJA AISI 4140 DENGAN METODE PACK CARBURIZING MEDIA ARANG BAMBU - Danel Saputro; Gery Setiadi; Supriyanto Wibowo (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2019)
Carburizing is a heat treatment process with the addition of carbon content to the metal surface. To obtain the microstructure and the desired properties of the metal can be obtained through the heating and cooling process at a certain temperature. To get a high hardness value after the carburization process of the workpiece, the quenching process is carried out, namely the rapid cooling process, so that the martensitic phase is obtained. AISI 4140 steel is one type of steel that is widely used in engine components such as piston pins. The piston pin is usually made of medium carbon steel AISI 4140. Based on its application this steel was developed with the aim of having mechanical properties especially hardness, strength and resistance to wear. This study tested the hardness of AISI 4140 steel before and after the solid carburizing process using 80% bamboo charcoal as carbon and 20% Barium Carbonate as a catalyst, with a holding time of 60, 90, and 120 minutes using oil quenching media. The results obtained showed an increase in the highest hardness value at the holding time of 120 minutes.